PENGARUH PERENDAMAN BIJI KAKAO KERING DAN BAHAN ALAT SANGRAI TERHADAP SIFAT FISIK DAN PROFIL SENYAWA VOLATIL KAKAO SANGRAI SERTA SIFAT SENSORIS COKELAT BATANG YANG DIHASILKAN - , YULIUS GAE LADA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to measure the effect of dry cocoa bean soaking and utilization of different materials of roasting instrument on physical properties, and volatile compound profile of roasted cocoa bean as well as to measure sensorial attributes of chocolate bar made from the beans. Factorial Randomized Design was used as research design on several factors: dry bean soaking (soaking and non-soaking), and roasting instrument material (alumunium, iron, and clay). Soaking was conducted using water for 2 hours to reduce cocoa beans acid content, while roasting using different kinds of instrument was carried out to obtain 2 â 3.5% moisture content. Results showed that cooking period using roasting instrument made from clay was shorter (50 minutes) with faster and higher temperature increase rate, followed by iron (70 minutes) dan aluminum (90 minutes). Dry cocoa bean soaking had significant effect on physical properties, which was on L* and ÎE value of color measurement, as well as chocolate bar sensorial attributes, particularly on cocoa distinctive aroma, acid taste and bitterness